PENERAPAN JUSTICE COLLABORATOR PADA TINDAK PIDANA NARKOTIKA (STUDI PUTUSAN PENGADILAN NEGERI JAKARTA UTARA NOMOR 770/Pid.Sus/2020/PN Jkt.Utr) - Anggi Octavelia Putri N; Ade Adhari (Jurnal Hukum Adigama, 2022)
Basically Justice Collaborator is a term in the criminal justice process in Indonesia which is a convict who cooperates with law enforcement to uncover a certain crime. One of the rarities that can be used in implementing effectiveness to eradicate organized crime networks is to use assistance from perpetrators who are insiders, and are directly involved in crimes that have been committed together with other perpetrators, especially narcotics criminals. With the presence of the Justice Collaborator, it is very important to uncover a narcotics crime case in Indonesia. This research is normative research. The research specifications used are prescriptive. The result of this study is that there is no application of reducing the prison term to the defendant Farida als Ida bint Abdul Rojak who has the status of a Justice Collaborator which is a reduction in the detention period is one of the rights that the defendant should be able to obtain. It was concluded that the application of the Justice Collaborator setting to the North Jakarta District Court Decision Number 770/Pid.Sus/2020/PN Jkt.Utr in the decision the application of the Justice Collaborator was not in accordance with the Justice Collaborator setting that had been stipulated in the United Nations Convention Against Corruption (UNCAC). ) 2003 which has been ratified by Indonesia with Law no. 7 of 2006, Article 37 paragraph (2), SEMA No. 4 of 2011 point 9 letter c, because the defendant has been applied as a Justice Collaborator but there is no reduction in detention time.